Metaphorical and metonymical uses of the Korean verb meok / Jeon Mi Ae - Jeon , Mi Ae (2016)
This qualitative study examines the concept of EAT associated with the verb meok- ‘eat’ in Korean. Data were collected from one online Korean newspaper and analysed based on the twin approaches of conceptual metaphor and conceptual metonymy. The Korean verb meok- evokes images of food, nourishment and enjoyable gustation. However, when the verb meok- is used metaphorically, particularly as part of compounds, it evokes expressions of unhappiness, with a negative connotation. As a simplex verb, meok- has been investigated in many studies. However, the investigation of meok- as a compound verb, which projects negativity in the metaphorical use, seems to be rare. Within the conceptual metaphor and metonymy theory of Lakoff and Johnson (1980), Lakoff (1993), Radden & Kövecses (1999) and Kövecses (2010), the present study is aimed at identifying the metaphorical and metonymical expressions of simplex and compound verbs of meok-. The study also examined how the adversity is exposed as a Korean socio-cultural factor in meaning construction of meok-. The analysis of the investigation found that the simplex meok- ‘eat’ is conceptualized metaphorically as EXPERIENCE IS EATING, HARBOURING THOUGHT IS EATING, ACQUIRING POSSESSION IS EATING, INTELLECTUAL SATISFACTION IS EATING and CONSUMING RESOURCE IS EATING. Metonymically, the simplex verb meok- ‘eat’ is conceptualized as EATING STANDS FOR LIFE containing EATING MEAL FOR THE STANDARD OF LIFE, EATING TYPES OF RICE OR WATER FOR TYPES OF LIFE and EATING ALONE FOR LIVING ALONE. Analysis further found that the most significant phenomenon of five (5) compound verbs of meok- ‘eat’ were saliently extended to the domains of DESTRUCTION as DESTRUCTION IS EATING. Two (2) compound verbs, kkameok- (peel.eat) and ppaemeok- (take out.eat), show partial destruction with DIMINISHING IS EATING and ELIMINATION IS EATING. The other three compound verbs, galgameok- (nibble.eat), jabameok- (slaughter.eat) and malameok- (mix.eat) showed whole destruction in DESTROYING RESOURCE IS EATING, DESTROYING HUMAN LIFE IS EATING and DESTROYING INSTITUTION IS EATING. Analysis also revealed that the concept of adversity is pervasive when used with the metaphorical uses of meok-, specifically in the UNPLEASANT EXPERIENCE in simplex meok- and in the DESTRUCTION of resources, human life, and social institutions in the compound verbs of meok-. The findings revealed that the most important identification of metaphorical uses of meok- is that, in UNPLEASANT EXPERIENCE, the agent is ‘affected agent’ motivated by the unpleasant bodily experience of internalization of food. Metonymical extensions of meok- were more strikingly associated with bap ‘cooked rice’, the Korean staple foodstuff. However, the Korean speaker’s cognitive choice of the metaphorical uses of compound verbs of meok- is ‘destruction’. It appears that the Koreans conceptualize the abstract destructive phenomena of the real world via the destructive concept of EAT. Findings also indicate that the sense of adversity with a critical and negative connotation serves as an alert and serves as a verbal warning through the use of metaphorical expressions of meok-.